Inheritance pattern of tetraploids pummelo, mandarin, and their interspecific hybrid sour orange is highly influenced by their phylogenomic structure - Aleza, Pablo; Garavello, Miguel Fernando; Rouiss, Houssem; Benedict, Ana Cristina; Garcia-Lor, Andres; Hernández, Maria; Navarro, Luis; Ollitrault, Patrick (Frontiers in Plant Science, 2023)
Citrus polyploidy is associated with a wide range of morphological, genetic, and physiological changes that are often advantageous for breeding. Citrus triploid hybrids are very interesting as new seedless varieties. On the other hand, tetraploid rootstocks promote adaptation to different abiotic stresses and promote resilience. Triploid and tetraploid hybrids can be obtained through sexual hybridizations using tetraploid parents (2x × 4x, 4x × 2x or 4x × 4x), but more knowledge is needed about the inheritance pattern of tetraploid parents to optimize the efficiency of triploid varieties and tetraploid rootstock breeding strategies. In this work, we have analyzed the inheritance pattern of three tetraploid genotypes: `Chandler´ pummelo (Citrus maxima) and `Cleopatra´ mandarin (C. reticulata), which represent two clear examples of autotetraploid plants constituted by the genome of a single species, and the `Sevillano´ sour orange, which is an allotetraploid interspecific hybrid between C. maxima and C. reticulata. Polymorphic SSR and SNP markers were used to estimate pa-rental heterozygosity restitution, and allele frequencies for centromeric loci were used to calculate the prefer-ential pairing rate related to the proportion of disomic and tetrasomic segregation. The tetraploid pummelo and mandarin displayed tetrasomic segregation. Sour orange evidenced a clear intermediate inheritance for five of the nine chromosomes (1, 2, 5, 7, and 8), a slight tendency towards tetrasomic inheritance on chromo-some 3, and intermediate inheritance with tendency towards disomy for chromosomes 4, 6, and 9. These results indicate that the interspecific, versus intraspecific phylogenomic origin, affects preferential pairing and, therefore, the inheritance patterns. Despite its high level of heterozygosity, the important preferential chromosome pairing observed in sour orange results in a limited diversity of the genotypic variability of its diploid gametes, and consequently, a large part of the genetic value of the original diploid sour orange is transferred to the tetraploid progenies.